Polypyrrole doped graphene nanocomposites as advanced positive electrodes for vanadium redox flow battery - Gursu, Hurmus; Ersozoglu, Mehmet Giray; Sarac, A. Sezai; Sahin, Yucel (SPRINGER, 2022)
Obtaining high catalytic activity and cycling stability of electrodes play a crucial role in vanadium redox flow batteries (VRFBs). However, some limitations, such as cost and required multiple synthesis procedures force us as an alternative solution; polypyrrole-sulfur-doped graphenes (PPy-SGs) are synthesized with a user-friendly electrochemical method and applied as a positive electrode for VRFB for the first time in the literature. Polypyrrole and sulfur-doped graphenes are formed on the graphite electrodes simultaneously in a 0.001 M pyrrole and 1.0 M H2SO4 solution at room temperature by a single-step cyclic voltammetry (CV) process. The electrode surface modification parameters such as the amount of S-doping, defect, and functionality rate of polymers and graphene are controlled by changing the cycle numbers at the scanned in a specific potential range. FTIR, Raman, XPS, SEM, and CV methods show the formation of PPy and sulfur-doped graphene layers on graphite electrode surfaces. The effects of PPy-SGs were investigated in VRFB for VO+2/VO2+ redox reactions. The electrochemical measurements of the PPy-SGs are carried out by CV and electrochemical impedance spectroscopy (EIS) analysis. According to CV results, PPy-SG20 demonstrates the best performance as a positive electrode material of the VRFB. This can be attributed to the significant improvement in the electrochemical kinetics by polypyrrole decorating graphene and enhancing active sites.
Keywords: STEP ELECTROCHEMICAL PREPARATION; PENCIL GRAPHITE ELECTRODE; POTENTIAL APPLICATION; OXIDE NANOCOMPOSITES; NANOTUBE COMPOSITES; CYCLIC VOLTAMMETRY; ANODE MATERIALS; PERFORMANCE; ENERGY; CATALYST; Engineering; Materials Science; Physics